Answered

At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Using the quadratic equation x2-3x+2=0 perform the following tasks:
solve by factoring.
solve by completing the square.


Sagot :

[tex]x^2-3x+2=0\\ x^2-x-2x+2=0\\ x(x-1)-2(x-1)=0\\ (x-2)(x-1)=0\\ x=2 \vee x=1\\\\\ x^2-3x+2=0\\ x^2-3x+\frac{9}{4}-\frac{1}{4}=0\\ (x-\frac{3}{2})^2=\frac{1}{4}\\ x-\frac{3}{2}=\sqrt{\frac{1}{4}} \vee x-\frac{3}{2}=-\sqrt{\frac{1}{4}}\\ x-\frac{3}{2}=\frac{1}{2} \vee x-\frac{3}{2}=-\frac{1}{2}\\ x=\frac{4}{2} \vee x=\frac{2}{2}\\ x=2 \vee x=1[/tex]